Exploring Pre-Service Chemistry Teachers’ Scientific Literacy on Environmental Issues through the Lens of the Nature of Science - Sholeh, Moh Ismail; Laksono, Pandu Jati; Jayanti, Etrie; Karina, Karina; Alinda, Okti Lia (PAEDAGOGIA, 2025)
This study aimed to investigate the level of scientific literacy and Nature of Science (NOS) conceptions among pre-service chemistry teachers in the context of environmental issues. This study adopted a mixed-methods approach combining descriptive surveys and semi-structured interviews. Participants were 72 pre-service chemistry teachers from universities in Palembang, Indonesia, selected through purposive sampling across academic levels. Data collection involved three instruments: a scientific literacy test on environmental issues, a NOS perception questionnaire, and qualitative interviews. The results showed that scientific literacy among participants was generally at a high level, with an average score of 86.00. Participants demonstrated strong competence in scientific content and practices, particularly on renewable energy, deforestation, and air pollution. However, lower scores were observed in contextual understanding, such as water quality and waste management. Regarding NOS conceptions, participants obtained an average score of 72.88%, indicating a high level of understanding, particularly on the tentativeness of scientific knowledge and the role of observation and inference. However, misunderstandings persist in areas such as creativity in science and the influence of social and cultural values. Interview results revealed a nuanced understanding of NOS, which is in line with theoretical frameworks that view science as empirical, tentative, and influenced by human creativity and social context. These insights underscore the importance of integrating NOS into science teacher education to foster critical thinking and contextual teaching of environmental issues